Delirium During Recovery in Patients With Severe COVID-19: Two Case Reports - Han, Dong; Wang, Chenyang; Feng, Xiaojing; Wu, Jing (Frontiers in Medicine, 2020)
Novel coronavirus disease (COVID-19) infected by SARS-CoV-2 has rapidly grown into pandemic around the world, leading to life-threatening respiratory, cardiovascular and cerebral complications. Here we reported two patients with severe COVID-19 who experienced delirium in the early stage of recovery and mental illness including fatigue, anxiety and post-traumatic stress disorder in the post-illness stage of COVID-19. Two patients were admitted to hospital due to clinical symptoms and feature of CT and were confirmed for COVID-19 by positive results of throat swab for SARS-CoV-2. Due to severe respiratory symptoms and low oxygenation index, they were transferred to ICU and received invasive mechanical ventilation and sedation. Hyperactive delirium was observed after being transferred out of ICU. Different treatment measures were taken in time. Delirium did not occur again in hospital, but they showed mental suffering, including fatigue, anxiety and post-traumatic stress disorder (PTSD), during the 5-month follow-up after discharge. Translational Significance 1)These two cases shared a cluster of specific characteristics and risk factors, including >60 years old, severe COVID-19, receiving invasive mechanical ventilation and related sedation, high dose and long-term corticosteroids treatment, delirium occurred transiently during recovery period with negative SARS-CoV-2 results and improved laboratory results. Those detailed manifestations with dynamic changes of diseases and related treatment might provide some clues to clarify the mechanism of psychiatric complications of COVID-19 and further inform targeted interventions. 2) Although there was transient delirium during early phase of recovery, moderate level of fatigue, anxiety and PTSD persisted for five months after discharge. Long-term follow-up of chronic neuropsychiatric sequelae of SARS-Cov-2 infection is as important as acute neuropsychiatric complication.